Time to endoscopy for acute upper gastrointestinal bleeding: Results from a prospective multicentre trainee‐led audit. Issue 2 (1st March 2019) - Siau, Keith; Hodson, James; Ingram, Richard; Baxter, Andrew; Widlak, Monika M; Sharratt, Caroline; Baker, Graham M; Troth, Tom; Hicken, Ben; Tahir, Faraz; Magrabi, Malik; Yousaf, Nouman; et al.
Abstract : Background: Endoscopy within 24 h of admission (early endoscopy) is a quality standard in acute upper gastrointestinal bleeding (AUGIB). We aimed to audit time to endoscopy outcomes and identify factors affecting delayed endoscopy (>24 h of admission). Methods: This prospective multicentre audit enrolled patients admitted with AUGIB who underwent inpatient endoscopy between November and December 2017. Analyses were performed to identify factors associated with delayed endoscopy, and to compare patient outcomes, including length of stay and mortality rates, between early and delayed endoscopy groups. Results: Across 348 patients from 20 centres, the median time to endoscopy was 21.2 h (IQR 12.0–35.7), comprising median admission to referral and referral to endoscopy times of 8.1 h (IQR 3.7–18.1) and 6.7 h (IQR 3.0–23.1), respectively. Early endoscopy was achieved in 58.9%, although this varied by centre (range: 31.0–87.5%, p = 0.002). On multivariable analysis, lower Glasgow–Blatchford score, delayed referral, admissions between 7:00 and 19:00 hours or via the emergency department were independent predictors of delayed endoscopy. Early endoscopy was associated with reduced length of stay (median difference 1 d; p = 0.004), but not 30‐d mortality (p = 0.344). Conclusions: The majority of centres did not meet national standards for time to endoscopy. Strategic initiatives involving acute care services may be necessary to improve this outcome.